A Narrative Inquiry Into Global Systems Change to Support Families When a Parent Has a Mental Illness - Isobel, Sophie; Allchin, Becca; Goodyear, Melinda; Gladstone, Brenda M. (Frontiers in Psychiatry, 2019)
The issues that confront families when a parent experiences mental illness are complex. This often means that multiple service systems must be engaged to meet families’ needs, including those related to intergenerational experiences of mental health and illness. A multisystem approach to public mental health care is widely recommended as a form of preventative intervention to address the effects of mental illness and its social, psychological and economic impact upon parents, children and families. Globally, a multi-systemic approach to care requires a change in the way systems are currently organized to support families, as well as the way systems are interacting with families, and with each other. This qualitative secondary analysis emerged from a primary study examining global systems change efforts to support families, including components of change that were common and considered successful in different countries. A narrative inquiry method was used to re-analyze the data by compiling the stories of change described by individuals from participant countries. The data was interrogated to ask questions about story content, and to identify who was telling the story and how they described important changes across different geographical and cultural contexts. The individual stories of eighty-nine system change experts from 16 countries were then compiled into a shared global narrative to demonstrate international progress that has occurred over time, toward multi-systemic change to support families where parents experience mental illness. While the global narrative demonstrates considerable overlap between pathways toward change, it is also important to document individual stories, as change pertains differently in different contexts. The individual stories and the global narrative illustrate how countries begin a journey toward change at different time points and may have various outcomes in mind when they commence. Study findings raise questions about the extent to which system change can be standardized across countries that have unique social, cultural, political, and economic features. This study provides several potential points of reference for countries considering, or currently undertaking system change to support families where a parent has a mental illness. It also provides an important story about international efforts undertaken to improve outcomes for families.